2001
DOI: 10.1111/j.1365-2516.2001.00530.x
|View full text |Cite
|
Sign up to set email alerts
|

von Willebrand factor in factor VIII concentrates protects against neutralization by factor VIII antibodies of haemophilia A patients

Abstract: We investigated the neutralization activity of factor VIII (FVIII) antibodies of 12 haemophilia A patients, acquired during treatment with plasma‐derived FVIII concentrates. All plasma samples, drawn in a clinically stable situation before any immunotolerance treatment, contained anti‐A2 domain and anti‐light‐chain FVIII antibodies. In nine patients’ plasmas, containing relatively high amounts of FVIII light‐chain antibodies (53–96%), a higher neutralization activity was found against recombinant FVIII concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 14 publications
2
33
0
Order By: Relevance
“…These findings have since been corroborated by others [12,13]. It has also been reported that VWF containing concentrates are less inhibited by inhibitors directed against the C2 region.…”
Section: In Vitro Observations On Antibody Reactivity With Fviii Concsupporting
confidence: 70%
“…These findings have since been corroborated by others [12,13]. It has also been reported that VWF containing concentrates are less inhibited by inhibitors directed against the C2 region.…”
Section: In Vitro Observations On Antibody Reactivity With Fviii Concsupporting
confidence: 70%
“…In this study, FVIII epitope specificity of inhibitors in this specific cohort seemed to be mainly located in the A2 domain or the light chain of FVIII with a potential effect on the results, although it does not appear to show a direct association between the antibody reactivity and the success to ITI with a VWF/FVIII complex concentrate, as suggested by other authors [15,17,18]. Anyway, the limited number of tested patients and the low sensitivity of the method do not allow us to draw definite conclusions.…”
Section: Discussionmentioning
confidence: 43%
“…VWF, beyond being the physiological FVIII-stabilizing protein [12,13] was shown to protect FVIII from neutralizing antibodies in vitro [14][15][16][17][18][19][20]. Accordingly, a better response to ITI was observed in two case series when ITI carried out with FVIII concentrates rich in VWF [21,22] was compared with ITI carried out with VWF-free FVIII concentrates either plasmaderived monoclonally purified or recombinant.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the higher the VWF content, the lower the inhibitor reactivity [30,31], presumably because of more complete blockade of antilight-chain antibodies [32]. The lower inhibitor reactivity observed with VWF-containing pdFVIII concentrates also translates into greater thrombin generation, according to recent in vitro studies [33], further substantiating a role for VWF in the management of inhibitor patients.…”
Section: Fviii/vwf Complex and The Management Of Patients With Inhibimentioning
confidence: 89%